Nicaragua : Poverty Reduction Strategy Paper: Progress Report on National Human Development Plan as of 2010. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper reports on progress made on Nicaragua's National Human Development Plan as of 2010. The operational goal for Nicaragua's National Human Development Plan is economic growth with increased employment and reduced inequality and poverty. The results for 2007-10 highlight a significant reduction in inequality among Nicaraguans based on better distribution of income and consumption. This has been possible owing to redistributive government policies with positive results, economic recovery, and positive economic growth in the midst of a world financial and economic crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet